Preseason maximal aerobic power in professional soccer players among different divisions - Marcos, M. A.; Koulla, P. M.; Anthos, Z. I. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to examine and compare the anthropometric, maximal oxygen uptake (VO2max), and positional differences of first division (D1) professional football players from players of second (D2) and third (D3) divisions in Cyprus football leagues. Four hundred twenty-one professional male football players participated in this study. All subjects underwent anthropometric and body composition evaluation. In addition, they performed an incremental cardiopulmonary exercise testing (CPET) on a treadmill for VO2max evaluation. The results were analyzed using 1-way analysis of variance, between subjects design revealing significant effects among the divisions. Tukey's honest significant difference (HSD) tests demonstrated that players from D1 scored significantly higher on VO2max and lasted significantly longer on the treadmill than participants of D2 and D3 (p = 0.05). Similar findings were demonstrated when D2 was contrasted against D3 players. Goalkeepers, defenders, and forwards demonstrated significantly higher anthropometric measurements, whereas wingers and midfielders demonstrated significantly higher VO2max (p = 0.05) than goalkeepers and defenders. The findings of this study clearly demonstrated that cardiovascular fitness, as determined by CPET, is an important fitness parameter that differentiates professional football players who play at a more advanced level. This could be attributed to the different seasonal schedules that allow for longer transition time for lower division players and thus favoring greater detraining effects. Emphasis should be given by fitness professionals on transition period training to minimize the detraining effects especially in lower divisions.